Relationship Between Self-Efficacy and Organizational Commitment in Nurses’ Early Careers - Takeuchi, Kumiko; Matsushita, Yumiko (JOURNAL OF JAPAN HEALTH MEDICINE ASSOCIATION, 2021)
To identify the relationship of changes in organizational commitment with individual self-efficacy and locus of control at three years after novice nurses start their career, we conducted a yearly questionnaire survey for three years for 329 new graduate nurses working in eight hospitals in the Kanto and Koshin-etsu area. The survey inquired on organizational commitment, general self-efficacy in individuals, and locus of control. The self-efficacy score, the locus of control score, and the organizational commitment sub-scale score (purpose, intention, utility, retention) were calculated, and a path diagram was created using each variable as an observation variable. The analysis subjects were 44 people who answered 3. The direct effect of self-efficacy on organizational commitment (purpose) was confirmed in the first year of the nurses’ career. In the second year, the direct effect of self-efficacy on organizational commitment (intention) was confirmed. However, in the third year, no direct effect on self-efficacy was found, only indirect, on organizational commitment (purpose) and organizational commitment (intention), for which locus of control mediated the effect. The results confirmed that strengthening and sustaining individual confidence could enhance organizational commitment immediately after the beginning of the career. However, after a few years, instead of organizational commitment being influenced only by strengthening individual confidence, a higher internal control for judgment (i.e., the ability to control one’s own action without depending on others) influenced organizational commitment.